Picolinic acids as β-exosite inhibitors of botulinum neurotoxin A light chain. Issue 84 (6th October 2016) - Bremer, Paul T.; Xue, Song; Janda, Kim D.
Abstract : A series of novel substituted picolinic acids demonstrated low micromolar inhibition of botulinum neurotoxin A light chain at the β-exosite. Abstract : In developing small-molecule inhibitors of botulinum neurotoxin serotype A light chain (BoNT/A LC), substituted picolinic acids were identified. Extensive investigation into the SAR of the picolinic acid scaffold revealed 5-(1-butyl-4-chloro-1 H -indol-2-yl)picolinic acid (CBIP), which possessed low micromolar activity against BoNT/A. Kinetic and docking studies demonstrated binding of CBIP to the β-exosite: a largely unexplored site on the LC that holds therapeutic relevance for botulism treatment.